Zerumbone and small interference RNA induced apoptosis in MCF-7 cell and mammary gland tumor via β-catenin protein inhibition - Fadl, Safa Abd Elfatah Amin (2013)
Extensive research is being conducted to identify therapeutic agents that can inhibit breast cancer cell proliferation through the induction of the apoptotic pathways. Among these is the Wnt/β-catenin pathway, of which β-catenin is one of the main oncogenes of the Wnt signaling pathway implicated in the adhesion of cancer and non-cancer cells. Several studies have shown that there is close linkage between Wnt/β-catenin pathways and tumourigenesis and dysregulation with increased cancer cell growth and survival. In this study, a natural compound, zerumbone (ZER) extracted from Zingiber zerumbet Smith was chosen as a potential anticancer compound. The objective of this study is to determine the efficacy of ZER as an inhibitor of breast cancer progression and the role of β-catenin in its anticancer effect. This study was conducted both in vitro on MCF-7 cells and in vivo in Sprague-Dawley rats induced to develop mammary gland tumor with LA7 and/or β- catenin knockdown LA7 cells. The MCF-7 cells and rats were treated with ZER and the ZER/β-catenin siRNA combination. β-catenin siRNA was used as a positive control to specifically inhibit expression and transcriptional activity of β-catenin. High-throughput screening of 500 apoptosis-related genes of the NFκB and p53 pathways were assessed in treated and untreated MCF-7 cells using the microarray profiles. The microarray analytical results were confirmed by real-time PCR and immunocytochemistry. In both the in vitro and in vivo studies, there was good correlation between β-catenin inhibition and apoptosis. The MTT assay, flow cytometry, confocal microscopy, and TUNEL assay confirmed that both ZER and siRNA induced apoptosis in MCF-7 cells while not adversely affecting normal cells. In the rat model, immunohistochemistry and real-time PCR also showed that ZER induced apoptosis in mammary gland tumor. The study showed that ZER and β- catenin siRNA treatments markedly decreased β-catenin-dependent gene expression and inhibition of MCF-7 cell proliferation. The study also showed the ZER/β-catenin siRNA combination treatment decreased β-catenin level in vivo. The results of this study suggest that both ZER and β-catenin siRNA express anticancer activities via targeting the Wnt/β-catenin signaling pathway. In conclusion, ZER and/or β-catenin siRNA could be used as potential compounds for the treatment of breast cancers.